Measuring Well-being among Engineering Undergraduates using Rasch Model Analysis - Zamri Khairani, Ahmad; Idris, Izazol; Effendi Ewan Mohd Matore, Mohd (International Journal of Engineering & Technology, 2018)
The purpose of this study is to calibrate undergraduatesâ€™ well-being. 378 engineering undergraduates provide responses for this study. An 8-item Flourishing Scale is employed to gauge the responses using the Rasch model analysis. Results show that one item need to be dropped since they did not meet the Rasch modelâ€™s expectations. Analysis on the remaining seven items showed that the undergraduates were least able to contribute to the happiness and well-being of others. In contrast they somewhat have positive well-being by endorsing that they have a purposeful and meaningful life. In addition, we discuss how to the findings might be helpful for university stakeholders to plan effective interventions for the undergraduates.Â